Strategic construal of down in English particle verbs - Geld, Renata (2012)
Particle verbs (PVs) are notoriously difficult for users of English as L2. This is due to their semantic complexity: the composite structure (the whole particle verb) is never construed as merely the union of the verb and the particle, nor do the verb and the particle appear as unmodified components in the composite whole (Langacker 2000: 94). The aim of this paper is to investigate the strategic construal of down in PVs and retest the findings proposed by Geld (2009, 2011) and Geld and Letica Krevelj (2011). We gave a questionnaire with 23 metaphoric meanings of a number of PVs to a sample of 68 Croats and 32 Mexicans, users of English as L2. As expected, the results suggest that the construal of PVs depends on: (1) the type of verb in the composite whole ; (2) the degree of informativeness of the particle ; (3) the level of users’ L2 proficiency and (4) the users’ L1. We will show that the users’ knowledge of down affects the overall construal of the PV construction, and at the same time depends on other language-internal and language-external factors. For example, the semantic contribution of down in break down ‘fail’ as opposed to down in put down ‘criticize somebody’ depends on semantic “lightness/heaviness” of the verb (cf. Geld 2009), as well as the user’s L1 and general language proficiency. Moreover, the basic up-down opposition may show similar tendencies as the in-out opposition. The first member of the in-out pair is more informative than the second: the number of types of construal of out in PVs outnumbered those of in with a particular verb (Geld 2009). By the same token, we expect the up-down relationship to be asymmetrical in this sense (data for up available in Geld and Letica Krevelj 2011). References Geld, Renata. 2009. “From Topology to Verbal Aspect: Strategic Construal of in and Out in English Particle Verbs”. Ph. D., Zagreb: Faculty of Humanities and Social Sciences, University of Zagreb. Geld, Renata. 2011. “Topological vs. lexical determination in English particle verbs (PVs).” Language Value 2 (2) (December 28): 49–75. Geld, Renata, and Stela Letica Krevelj. 2011. “Centrality of Space in the Strategic Construal of up in English Particle Verbs.” In Space and Time in Language, ed. Mario Brdar, Marija Omazić, Višnja Pavičić Takač, Tanja Gradečak-Erdeljić, and Gabrijela Buljan, 145–166. Frankfurt am Main, Berlin, Bern, Bruxelles, New York, Oxford, Wien: Peter Lang. Langacker, Ronald W. 2000. Grammar and Conceptualization. Berlin ; New York: Mouton de Gruyter.